Pour une analyse des textes iconiques en ethnologie - Gendreau, Andrée (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1982)
AbstractThis article surveys the various currents in iconographie analysis as an aim to develop a general methodology that would take into account the specific phenomena related to traditional art forms.